Medical biostatistics - Indrayan, Abhaya, author (Chapman & Hall/CRC biostatistics series, 2013)
The third edition of this acclaimed text focuses on the statistical aspects of medicine with a medical perspective, showing how biostatistics is a useful tool to manage medical uncertainties. This edition provides expanded coverage of topics and includes software illustrations. The author presents step-by-step explanations of statistical methods with the help of numerous real-world examples. Graphs and guide charts at the beginning of the book enable quick access to the relevant statistical procedure, and the comprehensive index makes it easier to locate terms of interest